PENGARUH STRUKTUR KEPEMILIKAN, UKURAN PERUSAHAAN, PROFITABILITAS, DAN FINANCIAL LEVERAGE TERHADAP INCOME SMOOTHING (Studi Empiris Pada Perusahaan Sektor Keuangan dan Perbankan yang Terdaftar di BEI Periode 2017 sampai dengan 2019) - Regina Indraswari Susmitha; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2022)
The financial and banking sector is an economic sector and has a huge role in funding. In addition, the financial and banking sector is more attractive to investors, and many of them are listed on the Indonesian stock exchange. It tends to improve the company's strategy to obtain funding from outside investors. Therefore, the company's management tends to carry out a strategy in earnings management to keep the fluctuations in profits looking stable. This study analyzes the effect of ownership structure, firm size, profitability, financial leverage on income smoothing.The population in this study was all financial and banking sectors listed on the Indonesia Stock Exchange for 2017 to 2019. Using a purposive sampling technique, we obtained 58 financial and banking sectors, and observational data in this study were 174 observational data. Hypothesis analysis and testing were carried out by logistic regression analysis using SPSS 25.The results showed that the variable ownership structure proxied by public ownership had no significant effect on income smoothing. The firm size had a significant effect on income smoothing. In contrast, the profitability variables proxied by net profit margin, financial leverage had no significant effect on income smoothing.